A slurry battery additive, a slurry electrode comprising the additive, and use thereof in a slurry battery

CN117012969BActive Publication Date: 2026-10-27SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311115726.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2026-10-27
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

[0004]本发明针对浆料电池目前存在的固体颗粒易沉降、电解液易挥发、极片厚度不均匀等问题,提供了一种能够均匀分散固体颗粒、抑制电解液挥发、增加浆料粘性的添加剂

Benefits of technology

[0011]本发明与现有技术相比有以下有益效果:本发明提供了一种基于浆料电池、能溶解在酯类电解液的多功能添加剂,该添加剂与电解液形成的胶状溶液一方面可以均匀粒径不一的颗粒、抑制电解液的挥发、增加浆料电池的加工性能,另一方面,可以改善石墨表面的SEI膜,提升电池的循环性能。添加方法简单、易于操作、适用于工业大规模生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a slurry battery additive, a slurry electrode comprising the additive, and application of the slurry electrode in a slurry battery, and a preparation method of the slurry battery additive. The preparation method comprises the following steps: dissolving ethyl cellulose with a molecular weight of 75000-250000 in an ester electrolyte to form a transparent gel solution, and preparing the slurry battery additive. The slurry battery additive is applied to a negative electrode sheet of a slurry battery. In the slurry battery, the slurry in the slurry battery can be uniformly mixed, the viscosity can be increased to improve the processability of the battery, and the interface side reaction of the battery can be inhibited to improve the cycle performance of the slurry battery. The battery is a high-energy battery, and at least one of the positive electrode or the negative electrode is in a slurry state. The additive can be directly added in the ester electrolyte, the adding process is simple and easy to operate, and the additive is suitable for industrial large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy, specifically relating to a multifunctional additive for slurry batteries and a slurry battery based on the additive. Background Technology

[0002] Population growth and changing lifestyles have increased consumption of coal, oil, and natural gas, making the transformation of the global energy structure imperative. The development and utilization of renewable energy sources such as wind, solar, and tidal power suffer from intermittency and instability; therefore, equipping large-scale energy storage facilities to ensure efficient storage and stable output of renewable energy is crucial. Electrochemical energy storage is widely used due to its advantages of low cost, long lifespan, high energy density, and high reliability.

[0003] The demand for high-energy batteries has driven continuous exploration in the fields of electrochemical storage materials and battery manufacturing processes. In recent years, scientists have made outstanding achievements in both positive and negative electrode materials. However, current battery designs are still based on the 1800 Voltaic pile, leading to the dilution of active materials and increased manufacturing costs. Slurry batteries combine the high energy density of secondary batteries with the flexibility and scalability of fuel cells and flow batteries. They store energy in a suspension of solid active compounds, achieving charge transfer through a diluted but permeated nano-conductive network. Slurry batteries achieve lithium-ion insertion and extraction in a semi-fluid state at the electrodes, completing the conversion of electrical and chemical energy. However, because slurry battery systems do not add binders to the electrodes or involve drying and rolling, the electrodes are in a low-compaction, electrolyte-rich environment, resulting in problems such as easy sedimentation of solid particles, easy evaporation of the electrolyte, and uneven electrode thickness. The study "Mechanical History Dependence in Carbon Black Suspensions for Flow Batteries: ARheo-Impedance Study" (DOI: 10.1021 / acs.langmuir.6b04322) uses conductive nanoparticles (Kejtien Black KB) to form a nano-network structure to prevent particle sedimentation. However, Kejtien Black KB consumes a large amount of lithium ions on the graphite anode side, reducing the first-cycle coulombic efficiency. Therefore, finding a multifunctional additive for slurry batteries to improve the dispersibility, uniformity, processability, and electrochemical performance of the graphite anode is of great significance. Summary of the Invention

[0004] This invention addresses the problems currently existing in slurry batteries, such as easy sedimentation of solid particles, easy evaporation of electrolyte, and uneven electrode thickness, by providing an additive that can uniformly disperse solid particles, inhibit electrolyte evaporation, and increase slurry viscosity.

[0005] The additive can be fully dissolved in ester electrolytes to form a gel-like solution. The additive can be fully dissolved in ester electrolytes to make the particles uniformly dispersed and increase the viscosity of the slurry. It is used to form an interfacial protective layer between the electrolyte and the graphite negative electrode during battery charging. The additive is ethyl cellulose (EC).

[0006] A slurry battery is a battery in which at least one of the positive or negative electrodes is in a slurry state. The slurry state is a solid-liquid mixture of active material powder, conductive additive powder, and electrolyte, including a gel state. Adding EC (electrolyte-based electrolyte) as an additive to the graphite negative electrode in a slurry battery solves problems such as uneven graphite particle dispersion, electrolyte evaporation, and improves processing performance. During charging, it forms a uniform and dense SEI film, enhancing its electrochemical performance. This uniform and dense protective film inhibits the deformation of the graphite negative electrode during charging and discharging, preventing further electrolyte decomposition and extending the battery's lifespan. This method improves upon the low electrode compaction density, solid-liquid phase separation, and uneven particle dispersion characteristics of slurry batteries. EC is dissolved in an ester-based electrolyte to form a gel-like solution. Adding this gel-like solution to the slurry increases its viscosity and inhibits electrolyte evaporation, thereby improving the battery's operability and the accuracy of its electrochemical performance.

[0007] The slurry battery of the present invention includes a lithium iron phosphate positive electrode, a graphite negative electrode, an ester electrolyte, and a separator between the positive and negative electrodes, with the above-mentioned additives added to one side of the graphite negative electrode slurry.

[0008] Preferably, the weight percentage of the slurry battery additive in the negative electrode graphite slurry is 0.07% to 3.5%.

[0009] The above-mentioned slurry battery organic electrolyte is a commercially available lithium-ion battery electrolyte, preferably 1.2M LiPF6, EC:EMC=3:7, 5%FEC.

[0010] The preparation method of a slurry battery includes the preparation of a positive electrode slurry, the preparation of a negative electrode slurry, the coating of the slurry positive electrode sheet, the coating of the slurry negative electrode sheet, and battery assembly. In the preparation of the negative electrode slurry, the negative electrode is a slurry with added slurry battery additives. Specifically, the process involves adding ethyl cellulose (EC) to an ester electrolyte to prepare an EC gel, which is a transparent, pale yellow state. 3-7 parts by weight of graphite negative electrode powder, 2-5 parts by weight of electrolyte, and 0.5-5 parts by weight of EC gel are mixed and homogenized using a Thinky planetary mixer to obtain the negative electrode slurry. LFP positive electrode powder, KB conductive agent, and commercial electrolyte are mixed at a mass ratio of 19:1:25 and homogenized using a Thinky planetary mixer to obtain the positive electrode slurry. The prepared LFP slurry and graphite slurry were transferred into the groove using a dropper. The mass of the slurry was measured by differential method. A diaphragm was then applied, and the N / P ratio (anode / anode unit area capacity ratio) was 0.8~3.0.

[0011] Compared with existing technologies, this invention offers the following advantages: It provides a multifunctional additive for slurry batteries that dissolves in ester-based electrolytes. The colloidal solution formed by this additive and the electrolyte can, on the one hand, uniformly distribute particles of varying sizes, inhibit electrolyte volatilization, and improve the processing performance of slurry batteries; on the other hand, it can improve the SEI film on the graphite surface, thereby enhancing the battery's cycle performance. The addition method is simple, easy to operate, and suitable for large-scale industrial production. Attached Figure Description

[0012] Figure 1 Comparison of solubility of additives 215000EC, CMC, and PVP in ester electrolyte 1.2M LiPF6, EC:EMC=3:7, and 5% FEC; Figure 2 Solubility diagram of additive 280000EC in ester electrolyte 1.2M LiPF6, EC:EMC=3:7, 5% FEC; Figure 3 Solubility diagram of additive 70000EC in ester electrolyte 1.2M LiPF6, EC:EMC=3:7, 5% FEC; Figure 4 Solubility diagram of additive EC in solvents dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC); Figure 5 Add a photo of graphite slurry with 0.7 wt.% EC. Figure 6 Add images of graphite slurry with 0.07 wt.% EC and 3.5 wt.% EC. Figure 7Add graphite cell performance data with 0.7 wt.% EC. Figure 8 Performance graph of graphite battery with 0.7 wt.% EC added to 1 M LiFSI ester electrolyte, EC:DMC:EMC = 1:1:1, and 1.9% FEC; Figure 9 Photograph of graphite paste without any additives; Figure 10 Performance graph of graphite battery without any additives; Figure 11 Photograph of graphite slurry with added conductive agent KB; Figure 12 Performance graph of graphite battery with added conductive agent KB; Figure 13 Comparison of volatility and viscosity between Example 5 and Comparative Example 9; Figure 14 Comparison of formation data between Example 5 and Comparative Examples 9 and 10; Figure 15 Performance graph of LiFePO4 / / Gr battery with 7% EC gel added to graphite anode. Detailed Implementation

[0013] The present invention will be further illustrated by the following examples. Experimental methods in the following examples that do not specify specific conditions are performed according to conventional methods and conditions.

[0014] Example 1 0.3500 g of ethyl cellulose (EC), sodium carboxymethyl cellulose (CMC), and polyvinylpyrrolidone (PVP) with a molecular weight of 215000 were added to 4.6500 g of 1.2 M LiPF6, EC:EMC = 3:7, 5% FEC electrolyte to prepare a 7% 215000EC gel solution (the molecular weight is not specified in the following examples, and all are 215000EC gel solutions, abbreviated as 7% EC gel solution). The gel solution is transparent and light yellow. CMC and PVP are insoluble in the electrolyte. CMC settles in the ester electrolyte, while PVP floats in the ester electrolyte (effect illustration 1). Comparative Example 2 0.3500 g of ethyl cellulose (EC) with a molecular weight of 280000 was added to 4.6500 g of 1.2 M LiPF6, EC:EMC = 3:7, 5% FEC electrolyte to prepare a 7% 280000EC gel solution. The gel solution was stirred for more than 24 hours and still did not completely dissolve, and the solution did not flow (effect figure 2).

[0015] Comparative Example 3 0.3500 g of ethyl cellulose (EC) with a molecular weight of 70000 was added to 4.6500 g of 1.2 M LiPF6, EC:EMC=3:7, 5% FEC electrolyte to prepare a 7% 70000EC solution (effect illustration 3).

[0016] Example 4 0.7000 g of ethyl cellulose (EC) with a molecular weight of 215000 was added to dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), and ethylene carbonate (EC), respectively. EC was dissolved in ester solvents (Figure 4).

[0017] Example 5 Preparation of graphite slurry: Graphite anode powder, electrolyte, and 7% EC slurry prepared in Example 1 were mixed evenly at a mass ratio of 5:4:1 to form the anode. The mixture was then thoroughly mixed using a Thinky planetary mixer. The EC content in the graphite slurry was 0.7% by weight, the slurry viscosity was 17830 cp, and the slurry was uniformly dispersed. (See Figure 5 for an example).

[0018] Comparative Example 6 Preparation of graphite slurry: Graphite anode powder, electrolyte, and 7% EC slurry prepared in Example 1 were mixed uniformly at a mass ratio of 5:4.9:0.1 to form the anode. The mixture was then homogenized using a Thinky planetary mixer. The weight percentage of EC in the graphite slurry was 0.07 wt.%, and the slurry viscosity was 690.3 cp. The graphite slurry was unevenly dispersed (see Figure 6, left).

[0019] Preparation of graphite slurry: Graphite anode powder and 7% EC slurry prepared in Example 1 were mixed evenly at a mass ratio of 1:1 to form the anode, and the mixture was stirred evenly using a Thinky planetary mixer. The weight percentage of EC in the graphite slurry was 3.5 wt.%, the slurry viscosity was 27690 cp, and the slurry formed agglomerates (see Figure 6, right).

[0020] Example 7 Preparation of graphite electrodes: The graphite slurry obtained in Example 5 was transferred into the groove using a dropper. The mass of the slurry was measured using the differential method. After covering with a separator, a coin-type lithium slurry battery was assembled using lithium metal as the counter electrode. The graphite electrode loading was 22.432 mg / cm³. 2 .

[0021] The voltage range is 0.01-1.5 V; the formation regime is 0.05 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.05 C constant current charge to 1.50 V; the cycling regime is 0.1 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.1 C constant current charge to 1.5 V. The cycling curve is shown in Figure 7.

[0022] Example 8 0.3500 g of ethyl cellulose (EC) with a molecular weight of 215000 was added to 4.6500 g of 1 M LiFSI electrolyte (EC:DMC:EMC = 1:1:1, 1.9% FEC) to prepare a 7% EC slurry. Graphite anode powder, electrolyte, and the 7% EC slurry were mixed uniformly at a mass ratio of 5:4:1 to form the anode. The prepared graphite slurry was transferred into a groove using a dropper, and the mass of the slurry was measured using a differential method. After covering with a separator, a coin cell lithium-ion battery was assembled using lithium metal as the counter electrode. The graphite electrode loading was 20.159 mg / cm³. 2 .

[0023] The voltage range is 0.01-2.0 V; the formation regime is 0.05 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.05 C constant current charge to 2.0 V; the cycling regime is 0.1 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.1 C constant current charge to 2.0 V. The cycling curve is shown in Figure 8.

[0024] Comparative Example 9 Preparation of graphite slurry: Graphite anode powder and electrolyte are mixed evenly at a mass ratio of 1:1 to form the anode. The mixture is then thoroughly mixed using a Thinky planetary mixer (see Figure 9 for an example).

[0025] Preparation of graphite electrodes: The prepared graphite slurry was transferred into the groove using a dropper tip. The mass of the slurry was measured using the differential method. After covering with a separator, lithium metal was used as the counter electrode to assemble a coin-type lithium slurry battery. The graphite electrode loading was 23.347 mg / cm³. 2 The voltage range is 0.01-1.5 V; the formation regime is 0.05 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.05 C constant current charge to 1.50 V; the cycling regime is 0.1 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.1 C constant current charge to 1.5 V. The cycling curve is shown in Figure 10.

[0026] Comparative Example 10 Preparation of graphite slurry: Graphite negative electrode powder, electrolyte and conductive agent KB are mixed evenly at a mass ratio of 45:1.5:53.5 to form the negative electrode (effect diagram 11).

[0027] Preparation of graphite electrodes: The prepared graphite slurry was transferred into the groove using a dropper tip. The mass of the slurry was measured using the differential method. After covering with a separator, lithium metal was used as the counter electrode to assemble a coin-type lithium slurry battery. The graphite electrode loading was 17.382 mg / cm³. 2 The voltage range is 0.01-1.5 V; the formation regime is 0.05 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.05 C constant current charge to 1.50 V; the cycling regime is 0.1 C constant current discharge to 0.01 V, rest for 5 minutes, and 0.1 C constant current charge to 1.5 V. The cycling curve is shown in Figure 12.

[0028] Comparison of operability between Example 5 and Comparative Example 9: After mixing, the slurries from Example 5, Comparative Examples 3, and 9 were placed open in a glove box. The change in slurry mass due to electrolyte evaporation was recorded over time. After normalization and comparison, it was found that the slurry with additive 215000EC had a significantly lower evaporation rate; after standing for 6 hours, its mass decreased by nearly 5%. This greatly improved the consistency of the slurry, which is beneficial for accurate subsequent weighing and calculation of the active material mass. The evaporation rate of the slurry with additive 750EC was almost the same as that of the slurry without additives. See Figure 13 for the effect. Comparison of formation data between Example 5 and Comparative Examples 9 and 10: Comparing the first-cycle electrochemical data of Example 5 with those of Comparative Examples 9 and 10, it can be seen that the conductive agent KB greatly reduces the first-cycle coulombic efficiency of the slurry graphite, which is not conducive to subsequent cycles; the additive EC can significantly increase the first-cycle coulombic efficiency and improve the electrochemical performance, as shown in Figure 14.

[0029] Example 11 Preparation of LFP slurry: LFP cathode powder, KB conductive agent, and commercial electrolyte were mixed uniformly at a mass ratio of 19:1:25 to form the cathode. The mixture was homogenized using a Thinky planetary mixer. Graphite slurry was prepared using the method described in Example 5. Preparation of LFP / / Gr batteries: The prepared LFP slurry was transferred into the groove using a dropper, and the mass of the slurry was measured using the differential method. After covering with a separator, the prepared graphite slurry was transferred into the groove using a dropper, and the mass of the slurry was measured using the differential method. After covering with a separator, the slurry was then covered with a separator. The N / P ratio (negative electrode / positive electrode unit area capacity ratio) was 1.223, and the positive electrode loading was 36.461 mg / cm³. 2 .

[0030] The voltage range is 2.50-3.8 V; the formation regime is 0.02 C constant current charging for 5 hours, 0.05 C constant current charging to 3.8 V, resting for 5 minutes, and 0.05 C constant current discharging to 2.50 V; the cycling regime is 0.1 C constant current charging to 3.8 V, 3.8 V constant voltage charging to 0.05 C, resting for 5 minutes, and 0.1 C constant current discharging to 2.5 V. The cycling curve is shown in Example 15.

Claims

1. The application of a slurry battery additive in a slurry electrode, characterized in that: The preparation method of the slurry battery additive is as follows: ethyl cellulose with a molecular weight of 75,000-250,000 is dissolved in an ester electrolyte to form a transparent light yellow colloid, and the slurry battery additive is obtained; the weight percentage of the slurry battery additive added to the negative electrode graphite slurry is 0.35%~3.5%.

2. The application according to claim 1, characterized in that: The solvent used in the ester electrolyte is at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, and ethylene carbonate.

3. The application according to claim 2, characterized in that: The ester electrolyte is 1.2M LiPF6, EC:EMC=3:7, 5% FEC or 1M LiFSI, EC:DMC:EMC=1:1:1, 1.9% FEC.

4. The application according to claim 1, characterized in that: After adding the battery additive to the slurry, the viscosity of the slurry is 750~25000 cp.

5. The application according to claim 1, characterized in that: The preparation method of negative electrode graphite slurry is as follows: 3-7 parts by weight of graphite negative electrode powder, 2-5 parts by weight of electrolyte, and 0.5-5 parts by weight of EC adhesive are mixed and uniformly mixed using a Thinky planetary mixer to obtain negative electrode graphite slurry.

6. The application according to claim 5, characterized in that: The preparation method of slurry battery includes the preparation of positive electrode slurry, preparation of negative electrode slurry, coating of slurry positive electrode sheet, coating of slurry negative electrode sheet, and battery assembly. In the preparation of negative electrode slurry, slurry battery additives are added to the negative electrode.

7. The application according to claim 6, characterized in that: The negative electrode sheet is made by coating a negative electrode paste.

8. The application according to claim 6, characterized in that: The preparation method of slurry battery is as follows: LFP positive electrode powder, KB conductive agent and commercial electrolyte are mixed at a mass ratio of 19:1:25 and mixed evenly using a Thinky planetary mixer to form positive electrode slurry. The prepared LFP slurry and graphite slurry are transferred into the groove using a dropper. The mass of the slurry is measured by differential method. A separator is then covered, and the N / P ratio of the positive and negative electrodes is 0.8~3.0.

Citation Information

Patent Citations

  • Conductive paste for solar cell electrode and solar cell manufactured by using same

    US20200098487A1